2019
DOI: 10.3389/fneur.2019.00286
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Survival Outcomes Following Reoperation in Recurrent Glioblastoma: Time to Consider the Timing of Reoperation

Abstract: Background: Glioblastoma multiforme (GBM) inevitably recurs, but no standard regimen has been established for recurrent patients. Reoperation at recurrence alleviates mass effects, and the survival benefit has been reported in many studies. However, in most studies, the effect of reoperation timing on survival benefit was ignored. The aim of this meta-analysis was to investigate whether reoperation provided similar survival benefits in recurrent GBM patients when it was analyzed as a fixed or time-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 49 publications
(114 reference statements)
2
35
0
4
Order By: Relevance
“…The favorable influence on outcome of second surgery at relapse, recently suggested by van den Bent's group [16], seems to be confirmed in our independent case series and extends the indications for second surgery, so far limited to improving the control of the epileptogenic outcome and obtaining a histological assessment of the possible glioma progression [32][33][34][35][36][37][38][39][40][41][42]. A recent meta-analysis of survival outcomes following reoperation in recurrent glioblastoma suggested a possible overestimation of the positive effects of the second surgery on patient outcomes when reoperation is considered a fixed variable [43]. Although our patient population consisted of LGG patients, it would be useful in the future to evaluate the opportunity of exploring the clinical benefits of reoperation, considering this covariate both as time-dependent or fixed.…”
Section: Discussionsupporting
confidence: 83%
“…The favorable influence on outcome of second surgery at relapse, recently suggested by van den Bent's group [16], seems to be confirmed in our independent case series and extends the indications for second surgery, so far limited to improving the control of the epileptogenic outcome and obtaining a histological assessment of the possible glioma progression [32][33][34][35][36][37][38][39][40][41][42]. A recent meta-analysis of survival outcomes following reoperation in recurrent glioblastoma suggested a possible overestimation of the positive effects of the second surgery on patient outcomes when reoperation is considered a fixed variable [43]. Although our patient population consisted of LGG patients, it would be useful in the future to evaluate the opportunity of exploring the clinical benefits of reoperation, considering this covariate both as time-dependent or fixed.…”
Section: Discussionsupporting
confidence: 83%
“…The recurrence of GBM is inevitable, in which management often tend to be unclear and case-dependent. Although re-radiation, re-resection, bevacizumab, and chemotherapy are still the most widely used therapies for treating recurrent GBM, the clinical benefit from these treatments is still not well established [46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…However, the tumor inevitably recurs, and standardized strategies for the treatment of recurrent glioma are lacking. The evidences of a favorable outcome regarding re-resection and re-irradiation are still poor (3). Therefore, systemic chemotherapy has been explored as a prospective option for glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Carmustine wafer implantation in GBM patients undergoing surgical resection is also thought to provide a therapeutic bridge during the period between surgical resection and onset of radiotherapy (6). Previous research assessing the effectiveness of carmustine wafer has found a significant increase in overall survival (OS) by 2-4 months in newly diagnosed GBM patients (3). Although the efficacy of carmustine administration is established in seminal trials, its safety remains controversial.…”
Section: Introductionmentioning
confidence: 99%